Elaboración de un Mapa Geomorfológico a escala 1:25000, mediante una Plataforma Sig de las Parroquias Catamayo y El Tambo perteneciente al Cantón Catamayo, Provincia de Loja, Ecuador - Mingo Morocho, Verónica Marisol (2020)
In recent years it has experienced an impressive cartographic evolution, so it is observed more and more the use of geographic information systems for the management and digital analysis of the land. Against this background the present research project entitled "development of a geomorphological map at 1:25 000 scale through a gis platform of the parishes of Catamayo and El Tambo belonging to the Canton Catamayo, Province of Loja, Ecuador", aimed at the quantitative characterization of the landscape through the automatic classification technique isodata on the basis of the digital elevation model, in the ENVI 5.3 software, was also complemented with 3d interpretation and field observations, Resulting in a total of 10 geoforms at the mesorelief level and 5 macrorelief level associated with 4 genetic classes. All of this is supported on a theoretical and methodological level. As a contribution to the physical management of its territory, it was also included the determination of the susceptibility to landslides, an important point to consider when carrying out human settlements. Therefore, this study contributes to the implementation of management plans that allow better expansion of the population, as well as an adequate use and occupation of the territory.